A Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material and its preparation method and application

By preparing Pt0.5Cu0.5/Ti-H2 photocatalyst material, using hydrogen treatment to regulate the surface atomic arrangement and defect sites of the alloy, the problem of unstudied effects of the activity of PtCu alloy under hydrogen treatment in the prior art is solved, and the problem of unstudied impact on PtCu alloy under hydrogen treatment is achieved. Efficient CO2 adsorption and electron transfer are used to significantly improve the photocatalytic CO2 reduction efficiency and catalyst stability.

CN118304901BActive Publication Date: 2025-01-03NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410442515.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2025-01-03
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

There is a lack of research on the effect of PtCu alloys in photocatalytic CO2 reduction reaction activity under hydrogen atmosphere treatment, and efficient photocatalysts are of great significance to carbon dioxide conversion.

Method used

Using the preparation method of Pt0.5Cu0.5/Ti-H2 photocatalyst material, Pt0.5Cu0.5 nanoparticles and TiO2 semiconductor were prepared, and temperature controlled calcination under hydrogen atmosphere was carried out to form Pt0.5Cu0.5/Ti-H2 catalyst. Hydrogen treatment regulates the surface atomic arrangement and defect sites of the alloy to improve CO2 adsorption and electron transfer capabilities.

Benefits of technology

The prepared Pt0.5Cu0.5/Ti-H2 catalyst has stable octahedral morphology and high CO2 adsorption capacity, significantly improves the photocatalytic CO2 reduction efficiency, generates fuel CH4 with higher calorific value, and improves the stability of the catalyst. and light response capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118304901B_ABST
    Figure CN118304901B_ABST
Patent Text Reader

Abstract

The present invention discloses a Pt 0.5 Cu 0.5 The invention relates to a preparation method of a / Ti-H2 photocatalyst material and its application, and belongs to the technical field of material preparation and photocatalytic CO2 reduction. 0.5 Cu 0.5 / Ti is treated with hydrogen to obtain Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material. The present invention obtains Pt 0.5 Cu 0.5 / Ti‑H2 photocatalyst materials and applied them in the field of photocatalytic CO2 reduction. 0.5 Cu 0.5 / Ti‑H2 significantly increased the Pt 0.5 Cu 0.5 / Ti photocatalyst efficiency. This invention simulates natural photosynthesis to reduce CO2 into high value-added fuels, providing some ideas for the future design of highly active photocatalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material preparation and photocatalytic CO2 reduction, and specifically relates to a Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material and its preparation method and application. Background Art

[0002] With the rapid development of industry and the burning of fossil fuels, CO2 emissions have increased year by year, and the resulting environmental problems have become increasingly serious. Therefore, controlling carbon emissions has become a hot topic. Photocatalytic reduction of CO2 to chemicals with high added value by simulating natural photosynthesis is a promising strategy to enrich energy supply and reduce carbon dioxide emissions. Therefore, the development of efficient photocatalysts is of great significance for carbon dioxide conversion.

[0003] PtCu alloys are widely used in photocatalytic CO2 reduction reactions due to their tunable surface atomic arrangement and strong CO2 adsorption capacity. In addition, according to literature reports, heat treatment under a hydrogen atmosphere is an effective method to promote electron-hole separation in photocatalysts. In addition, the defect sites generated by hydrogen-treated catalysts may be active sites for the reaction. However, there is currently no research on the effect of hydrogen atmosphere treatment on the activity of PtCu alloys for photocatalytic CO2 reduction. Summary of the invention

[0004] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material. In addition, another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned material. The final technical problem to be solved by the present invention is to provide the Pt 0.5 Cu 0.5 / Application of Ti-H2 photocatalyst materials in photocatalytic reduction of CO2.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A Pt 0.5 Cu 0.5 Preparation method of Ti-H2 photocatalyst material: first prepare Pt 0.5 Cu 0.5 Nanoparticles; then prepare TiO2 semiconductor; mix Pt in solution 0.5 Cu 0.5 Nanoparticles and TiO2 semiconductor, evaporation and drying to obtain Pt 0.5 Cu 0.5 / Ti; Pt was calcined in a tubular furnace at a temperature not lower than 200°C under a hydrogen atmosphere0.5 Cu 0.5 / Ti is not less than 2h, get Pt 0.5 Cu 0.5 / Ti-H2 catalyst.

[0007] The Pt 0.5 Cu 0.5 / The preparation method of Ti-H2 photocatalyst material, the preparation method of TiO2 semiconductor is as follows: put anatase phase TiO2 in a porcelain round dish, and then put it in a muffle furnace and calcine it at 450℃ for 2h. After the calcination, cool it to room temperature and take it out for use.

[0008] The Pt 0.5 Cu 0.5 / Preparation method of Ti-H2 photocatalyst material, Pt 0.5 Cu 0.5 The preparation method of the nanoparticles is as follows: platinum acetylacetonate and copper acetylacetonate are dissolved in a mixed solution of oleic acid and oleylamine, and the mixed solution is vacuumed and filled with nitrogen for multiple times under magnetic stirring; the temperature is raised to 130°C, and 100 mg of hexacarbonyl tungsten is added; the temperature is then raised to 240°C and maintained for 40 minutes; the above solution is cooled to room temperature and the resulting precipitate is centrifuged, the centrifugal solvents are n-hexane and ethanol, and finally the black product obtained by four centrifugations is dispersed in n-hexane.

[0009] The Pt 0.5 Cu 0.5 / Method for preparing Ti-H2 photocatalyst material, wherein the molar ratio of platinum acetylacetonate and copper acetylacetonate is 1:1, and the total loading amount is 1wt.%.

[0010] The Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material preparation method, the volume ratio of the mixed solution of oleic acid and oleylamine is 9:1.

[0011] The Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material preparation method, the amount of hexacarbonyl tungsten used is 100 mg.

[0012] The Pt 0.5 Cu 0.5 / The preparation method of Ti-H2 photocatalyst material, the vacuum drying condition is 60°C vacuum drying for 12 hours.

[0013] The Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material preparation method, the calcination conditions are heating rate of 5 ° C / min, heating to 200 ° C and then keeping constant temperature for 2 hours.

[0014] The Pt prepared by the method 0.5 Cu 0.5 / Ti-H2 photocatalyst material.

[0015] The Pt 0.5 Cu 0.5 / Application of Ti-H2 photocatalyst materials in photocatalytic CO2 reduction.

[0016] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0017] 1) This invention uses atmosphere treatment to regulate Pt for the first time 0.5 Cu 0.5 / Ti, prepared Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst materials, compared with the photocatalytic alloys supported on TiO2 semiconductors reported in the literature, such as PtCu / Ti, PdCu / Ti alloys, etc. 0.5 Cu 0.5 / Ti-H2 exposes specific crystal planes and has a stable morphology. It mainly exposes the (111) crystal plane, presents an octahedral morphology, and maintains the octahedral structure of the (111) crystal plane after hydrogen treatment. In addition, compared with the materials reported by previous researchers, the alloy has a lower loading and better catalytic performance.

[0018] 2) Pt prepared by the present invention 0.5 Cu 0.5 / Ti-H2 photocatalyst material has a strong CO2 adsorption capacity, which is more conducive to improving the efficiency of photocatalytic CO2 reduction and generating CH4, a fuel with higher calorific value.

[0019] 3) The hydrogen-treated Pt prepared by the present invention 0.5 Cu 0.5 / Ti-H2 photocatalyst material has strong Pt 0.5 Cu 0.5 The strong interaction with TiO2 makes PtCu have more favorable electron distribution and transfer ability, which ultimately leads to the adsorbed CO2 gaining more electrons.

[0020] The present invention obtains Pt by hydrogen treatment 0.5 Cu 0.5 / Ti-H2 photocatalyst material, and used it for the first time in the photocatalytic CO2 reduction reaction. 0.5 Cu 0.5 / Ti photocatalyst materials show unique advantages in the photocatalytic reduction of CO2 reaction. In order to further improve the 0.5 Cu0.5 / Ti-H2 catalytic performance, improve its light response ability, the Pt constructed by the present invention 0.5 Cu 0.5 / Ti-H2 photocatalyst material can not only utilize Pt 0.5 Cu 0.5 / Ti photocatalyst material has unique atomic arrangement structure and good catalytic performance, and can provide CO2 adsorption sites and photoelectrons required for the reaction by virtue of defect sites and good light absorption ability generated during hydrogen treatment. 0.5 Cu 0.5 The interaction between TiO2 and Pt 0.5 Cu 0.5 The transmission capacity between them can further improve the performance of photocatalytic reduction of CO2 reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM image of the prepared sample;

[0022] Figure 2 is the XRD spectrum of the prepared sample;

[0023] Figure 3 is the UV-vis DRS spectrum of the prepared sample;

[0024] Figure 4 is the FTIR spectrum of the prepared sample;

[0025] Figure 5 is the Raman spectrum of the prepared sample;

[0026] Figure 6 is the photocurrent diagram of the prepared sample;

[0027] Figure 7 Impedance spectrum of the prepared sample;

[0028] Figure 8 CO2-TPD diagram of the prepared sample;

[0029] Fig. 9 The photocatalytic reduction of CO2 performance comparison chart of the prepared samples and the catalyst stability test chart;

[0030] Fig.10 This is a comparison chart of the photocatalytic reduction of CO2 performance of samples with different element molar ratios. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described below in conjunction with specific embodiments.

[0032] Example 1 Preparation of Pt 0.5 Cu 0.5 Nanoparticles

[0033] Weigh 39 mg of platinum acetylacetonate and 26 mg of copper acetylacetonate, dissolve in a mixed solution of oleic acid and oleylamine (18 mL of oleylamine and 2 mL of oleic acid), and vacuum and fill the mixed solution with nitrogen several times under magnetic stirring. After exhausting the air in the three-necked flask, heat it to 130°C and add 100 mg of hexacarbonyl tungsten. Then heat it to 240°C and keep it for 40 minutes. After cooling the above solution to room temperature, centrifuge the resulting precipitate. The centrifugal solvent is 5 mL of n-hexane and 30 mL of ethanol. Finally, the black product obtained by four centrifugations is dispersed in n-hexane.

[0034] Example 2 Preparation of TiO2 Semiconductor

[0035] Weigh 3 g of rutile phase TiO2 into a round dish, place it in a muffle furnace, heat it to 450°C at a heating rate of 5°C / min in an air atmosphere, maintain it at this temperature for 2 hours, and obtain a TiO2 semiconductor after cooling to room temperature.

[0036] Example 3 Preparation of Pt 0.5 Cu 0.5 / Ti-H2 catalyst

[0037] The suspension obtained in Example 1 was magnetically stirred for 20 minutes. Then 1.29 g of the TiO2 semiconductor in Example 2 was added to the solution and stirred for 30 minutes to mix it evenly. The mixed suspension was placed on a rotary evaporator at a speed of 100 rpm for 1 hour. The final solid powder was vacuum dried at 60°C for 12 hours to obtain Pt 0.5 Cu 0.5 / Ti. 0.5 Cu 0.5 / Ti was introduced into a tubular furnace with hydrogen atmosphere, heated to 200°C at a heating rate of 5°C / min, and maintained at this temperature for 2h, finally obtaining Pt 0.5 Cu 0.5 / Ti-H2 catalyst.

[0038] The samples were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), ultraviolet visible diffuse reflectance spectroscopy (UV vis DRS), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy (Raman), photocurrent, electrochemical impedance spectroscopy and CO2 temperature programmed desorption (CO2-TPD). The results are as follows:

[0039] Figure 1 Pt 0.5 Cu 0.5 / Ti and Pt0.5 Cu 0.5 / Ti-H2 TEM images, both samples showed octahedral outlines, and the exposed crystal planes were 0.21 nm, which was attributed to the (111) crystal plane of the PtCu alloy, indicating that the alloy was successfully prepared and the hydrogen treatment did not change its morphology and exposed crystal planes.

[0040] Depend on Figure 2 Pt 0.5 Cu 0.5 / Ti and Pt 0.5 Cu 0.5 Comparing the XRD images of / Ti-H2, the two samples showed anatase phase TiO2, and no diffraction peaks attributed to PtCu alloy appeared, indicating that PtCu alloy was uniformly dispersed on the support surface.

[0041] according to Figure 3 Pt 0.5 Cu 0.5 / Ti and Pt 0.5 Cu 0.5 / Ti-H2 UV-vis spectrum, it can be seen that hydrogen treatment did not change the Pt 0.5 Cu 0.5 / Ti's light absorption capacity, which shows that hydrogen treatment does not change the properties of the semiconductor itself.

[0042] Figure 4 FTIR spectrum, 1000-1100cm -1 and 520-800cm -1 The broad peaks at represent the vibration of Ti-O bonds and Ti-O-Ti bonds in the TiO2 molecule. 0.5 Cu 0.5 / Ti-H2, the vibrations of Ti-O and Ti-O-Ti bonds are weakened, which indicates that the Ti and O on the surface may form bonds with Pt and Cu. Therefore, it is believed that TiO2 and Pt 0.5 Cu 0.5 An interaction occurred.

[0043] Figure 5 Pt 0.5 Cu 0.5 / Ti and Pt 0.5 Cu 0.5 / Ti-H2 Raman spectrum, where the A1g peak is caused by the asymmetric bending vibration of O-Ti-O. It is not difficult to see that after hydrogen treatment, Pt 0.5 Cu 0.5 / Ti-H2 A1g peak intensity is significantly weakened, indicating that the surface Ti-O bonding is reduced, and part of it participates in the coordination with Pt and Cu. This is also consistent with the FTIR results.

[0044] Figure 6 and Figure 7 Pt 0.5 Cu 0.5 / Ti and Pt 0.5 Cu 0.5 / Ti-H2 photocurrent and impedance diagram. It can be concluded that compared with Pt 0.5 Cu 0.5 / Ti,Pt 0.5 Cu 0.5 / Ti-H2 has a larger photocurrent and a smaller impedance value, indicating that the separation efficiency and utilization rate of photogenerated electrons are significantly enhanced. 0.5 Cu 0.5 Although the strong interaction with TiO2 does not change the light absorption capacity, it can serve as a transmission bridge for photoelectrons and accelerate the separation of photogenerated electrons and holes.

[0045] according to Figure 8 Pt 0.5 Cu 0.5 / Ti and Pt 0.5 Cu 0.5 / Ti-H2 CO2-TPD, the CO2 desorption peak area becomes larger and moves toward the high temperature direction after hydrogen treatment, indicating that the defects caused by hydrogen treatment make Pt 0.5 Cu 0.5 / Ti-H2's CO2 adsorption capacity increases and stronger CO2 adsorption occurs.

[0046] Example 4: The photocatalyst prepared in Example 1-3 is applied to reduce CO2

[0047] The photocatalytic CO2 reduction reaction test is carried out in a closed reactor. The specific steps are as follows:

[0048] 20 mg of the prepared catalyst powder was dispersed in 1 mL of deionized water, and then evenly dispersed on a quartz sand plate reaction dish with a diameter of 4.2 cm, and finally the reaction dish was placed in a 100 mL stainless steel reactor with a quartz light-transmitting window with a diameter of 4.5 cm on the top. After the reaction container was sealed, 0.2 MPa of high-purity CO2 gas was introduced into it, and a 280W xenon lamp was turned on for 6 hours of photocatalytic reaction. The product was detected online by gas chromatography (model GC-7920), and the detection time interval was 1 hour. The product yield was calculated by the following two formulas:

[0049]

[0050]

[0051] Among them, A tis the peak area of ​​CO or CH4, A CO and A CH4 Represents the peak area of ​​CO and CH4 standard gas with a concentration of 30 ppm, [CO] S and [CH4] S represents the concentration of CO and CH4 standard gas (30ppm) respectively. P, V and T represent the pressure (Pa) and volume (m 3 ) and temperature (K). R represents the molar gas constant. m is the mass of the photocatalyst (g).

[0052] Fig. 9 (A) is Pt 0.5 Cu 0.5 / Ti and Pt 0.5 Cu 0.5 Comparison of the catalytic performance of / Ti-H2 for CO2 reduction under full spectrum irradiation. The results show that compared with Pt 0.5 Cu 0.5 Compared with Ti, the Pt 0.5 Cu 0.5 / Ti-H2 has better photocatalytic reduction performance, which increases the output of CH4 fuel with higher calorific value, thereby improving the photocatalytic resource utilization of CO2. In addition, Fig. 9 (B) is a stability test. In the case of no sacrificial agent and continuous 24-hour test, Pt 0.5 Cu 0.5 / Ti-H2 shows higher stability.

[0053] Example 5 Comparative experiment of different element molar ratios

[0054] According to Examples 1-3, a comparative experiment of different element molar ratios was carried out, and the molar ratios of Pt and Cu were 2:3, 1:1, 3:2 and 4:1 respectively. The results are as follows Fig.10 As shown in the figure, after hydrogen treatment, the photocatalytic reduction performance of all samples to produce CH4 was significantly improved.

Claims

1. Pt 0.5 Cu 0.5 / Application of Ti-H2 photocatalyst material in photocatalytic CO2 reduction, characterized in that, The Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material is prepared by the following method: First prepare Pt 0.5 Cu 0.5 Nanoparticle suspensions; Then prepare the TiO2 semiconductor; mix Pt 0.5 Cu 0.5 Nanoparticles and TiO2 semiconductor, evaporation, vacuum drying to obtain Pt 0.5 Cu 0.5 / Ti; Pt was calcined in a tubular furnace at a temperature above 200°C under a hydrogen atmosphere 0.5 Cu 0.5 / Ti 2h or more, Pt 0.5 Cu 0.5 / Ti-H2 photocatalyst material; Pt 0.5 Cu 0.5 The preparation method of the nanoparticle suspension is as follows: 39 mg of platinum acetylacetonate and 26 mg of copper acetylacetonate are dissolved in a mixed solution of oleic acid and oleylamine, and the mixed solution is vacuumed and filled with nitrogen for multiple times under magnetic stirring; the temperature is raised to 130°C, and 100 mg of tungsten hexacarbonyl is added; the temperature is then raised to 240°C and maintained for 40 minutes; the obtained solution is cooled to room temperature and the obtained precipitate is centrifuged, and the centrifugal solvents are n-hexane and ethanol, and finally the black product obtained by four centrifugations is dispersed in n-hexane; The volume ratio of oleic acid to oleylamine is 9:1; The preparation method of TiO2 semiconductor is as follows: placing anatase phase TiO2 in a porcelain round dish, and then placing it in a muffle furnace and calcining it at 450°C for 2 hours. After the calcination is completed, it is cooled to room temperature and taken out for use.

2. The use according to claim 1, characterized in that: The vacuum drying condition is 60° C. vacuum drying for 12 h.

3. The use according to claim 1, characterized in that: The calcination conditions in the tubular furnace are as follows: the heating rate is 5°C / min, and the temperature is kept constant for 2 h after the temperature reaches 200°C.